Heat Flux Kondensasi pada Media Arang Tempurung Kelapa (Cocos Nurifera) - Yohanes, Eko; Soeparman, Sudjito; Siswanto, Eko (Jurnal Rekayasa Mesin, 2014)
Condensation in porous media can be applied for alternative of control air humidity. Which one for each temperature variation need an hour to complete the experiments.Coconut shell charcoal installed in the condensator chamber with height 2 cm. warm vapour then entered the condensator chamber. We observed temperature distribution and absorbed warm vapour among the condensation chamber and analyze how absorbed vapour will formed. The results showed forced convection that unown from value Gr/Re <1. With the results of the heat flux at the highest point of T2 and T1. With Lyapunov Exponents M = log 2 2(...) is always a positive value, due to increased average condensate growing over time and increase included in chaos areas because there is no repetition in each attractor.Keywords : Heat Flux, Coconut Shell Charcoal and Eksponen Lyapunov.